Peningkatan Pemahaman Nilai-Nilai Akhlak Mulia Melalui Penerapan Metode Pembelajaran Roleplaying Mata Pelajaran PAI SMAN 6 Karawang - Suci Rahmawati; Tsazkiya Aqiila Salsabila; Widiarti Permana Sari; Septi Permatasari; Wildan Ahmad; Siti Khulasoh (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
The aim of this research is to determine how effective role-playing is in improving students' understanding of noble moral values in the subject of Islamic Religious Education (PAI) at SMAN 6 Karawang. The background of this research is the importance of internalizing noble morals among students, which requires an active and contextual learning approach. This qualitative approach uses a classroom action research design (CAR). A total of thirty students from class XI-I are the subjects of the study. Observation, tests, and documentation are the data collection methods. The results of the study show that using role-playing methods can enhance students' understanding of moral values such as honesty, trustworthiness, humility, and keeping promises. This is evidenced by the increase in the average scores of students in each cycle, as well as the increase in student participation and positive attitudes during the learning process. Therefore, role playing has proven to be an effective learning approach in teaching noble moral values in Islamic secondary schools.